microRNA-183–5p induces cell density-dependent apoptosis through the regulation of Presenilin 2 - Yuki Yabuuchi; Yosuke Matsuno; Kai Yazaki; Wei Zhen Ting; Kengo Nishino; Sosuke Matsumura; Kenya Kuramoto; Kazufumi Yoshida; Masashi Matsuyama; Takumi Kiwamoto; Yuko Morishima; Nobuyuki Hizawa (European Journal of Cell Biology)
Cells undergo apoptosis under dense culture condition to maintain homeostasis. Impaired apoptosis may contribute to the excessive accumulation of pathogenetic cells in such diseases as cancer and organ fibrosis. Elucidating the molecular mechanisms regulating cell density-dependent apoptosis may provide novel therapeutic strategy against these diseases. We have reported Notch signaling, activated by γ-secretase under dense culture condition, regulates cell density-dependent apoptosis through the induction of IL-6. Presenilin 2 (PSEN2) is a subunit of γ-secretase and has been shown to modulate apoptosis. The role for PSEN2 in cell density-dependent apoptosis and Notch signaling activation, however, remains unclear. Here, we show a crucial role for PSEN2 in the regulation of cell density-dependent apoptosis in NIH 3T3 cells. PSEN2 protein primarily existed as C-terminal fragment (CTF). PSEN2 CTF expression was upregulated as cell density increased. PSEN2 regulated the development of apoptosis, which is accompanied by increased Bcl-2 expression, decreased Bax expression, and activated PI3K/Akt pathway. PSEN2 is predicted to be targeted by microRNA-183–5p (miR-183–5p) by several algorithms. We verified miR-183–5p directly regulates PSEN2 expression and induces apoptosis. In conclusion, our results demonstrate a crucial role of PSEN2 and its regulation by miR-183–5p in the regulation of cell density-dependent apoptosis.